2021
DOI: 10.1111/1440-1681.13589
|View full text |Cite
|
Sign up to set email alerts
|

GAB1 alleviates septic lung injury by inhibiting the TLR4/ NF‐κB pathway

Abstract: Sepsis is a systemic disease caused by bacterial or viral infections. SARS-COV-2, which is still rampant around the world at the end of 2019, can also cause severe viral sepsis. 1,2 Acute lung injury (ALI) is one of the most common complications of sepsis, which can lead to acute respiratory distress syndrome (ARDS) with high mortality. 3 Acute lung injury in sepsis is related to increased pulmonary vascular permeability, alveolar epithelial cell damage, and lung immune inflammatory cell activation and infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Moreover, Wang et al showed that alveolar epithelium-specific GAB1 knockout perturbed surfactant homeostasis and predisposed mice to LPS-induced ALI [ 48 ]. In contrast, GAB1 overexpression dramatically reduced LPS-induced inflammation and apoptosis, thereby alleviating LPS-induced ALI in mice [ 53 ]. von Holleben et al previously identified GAB1 was a potential binding partner of SAMSN1 using BLAST data based search with its SH3 domain [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Wang et al showed that alveolar epithelium-specific GAB1 knockout perturbed surfactant homeostasis and predisposed mice to LPS-induced ALI [ 48 ]. In contrast, GAB1 overexpression dramatically reduced LPS-induced inflammation and apoptosis, thereby alleviating LPS-induced ALI in mice [ 53 ]. von Holleben et al previously identified GAB1 was a potential binding partner of SAMSN1 using BLAST data based search with its SH3 domain [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we, for the first time, reported that cardiac Gab1 overexpression could inhibit DOX-induced ROS, inflammatory response, and apoptosis, which was similar to what was previously reported. 25–27…”
Section: Discussionmentioning
confidence: 99%
“…They found that Gab1 expression was markedly decreased after LPS stimulation, and Gab1 overexpression significantly decreased levels of macrophages, neutrophils, and inflammatory factors caused by LPS in bronchoalveolar lavage fluid. 27 Combining the above clues, Gab1 may be an upstream mediator of cardiac ROS, apoptosis, and inflammation induced by several pathological stimuli. However, there is no available data about the role of Gab1 in DOX-induced ROS, apoptosis, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation